Branding of North Sulawesi tourism through the hexagon of competitive identity - Menayang, Alfred Pieter; Marta, Rustono Farady (Faculty of Communications Science, Dr. Soetomo University, 2020)
This research was motivated by the disappointment of the North Sulawesi Provincial Government, and its people because none of the tourism destinations in the area was included in the list. Phenomenally, North Sulawesi Province in 2018 was named as the Province with best tourism performance in Indonesia, and in middle of 2019, the Likupang Tourism Special Economic Zone in North Sulawesi was designated as one of the five Super Priority Tourism Destinations. This study used the constructivist paradigm with qualitative research methodology aimed to analyse the success of a local government in tourism branding. The theoretical framework of Nation Brand Hexagon was adopted to the provincial level, i.e., the hexagon of competitive identity was used as the parameter to evaluate the outcomes of Branding North Sulawesi Tourism. The core finding of this study was the intertwining of three factors to support the success of North Sulawesi tourism branding, namely: lobbying to the central government, multi-stakeholder involvement management, and integrated marketing communication. This study aimed to understand the importance of Government Marketing for branding North Sulawesi Tourism through the Hexagon of Competitive Identity, namely: governance, investment and immigration, tourism, exports, culture and heritage, and people. From these findings, it can be concluded that the North Sulawesi Provincial Government has performed optimally and simultaneously the hexagon of competitive identity needed in branding its tourism destination, in doing its roles as a lobbyist, as a marketer, and as Catalyst of North Sulawesi Tourism Branding.